A Systematic Mapping of Games for Teaching Programming - Vieira, Sávio L.; Fonseca, Rafael C.; Souza, Maurício R. A. (Anais do Workshop sobre Educação em Computação (WEI); 2024: Anais do XXXII Workshop sobre Educação em ComputaçãoDO - 10.5753/wei.2024.2930, 2024)
The use of games as a teaching tool is not new. In 2022, it became compulsory to teach computer science in elementary and high schools in Brazil. Serious games or educational games are a great approach to diversify teaching. The use of games is proving to be a viable methodology to complement teaching strategies. This systematic mapping aims to identify, analyze, and synthesize existing games for teaching programming. We identified 94 primary studies from 2016 to 2023. They were then classified by type of game and the learning domain and learning objective were mapped, related to categories within the programming discipline.